Description Of Avian Bio-Diversity Of Damdamma Jheel In Gurgaon District In Haryana, India - Rohtash Chand Gupta; Tirshem Kumar Kaushik (Journal of Tropical Life Science, 2012)
Damdamma Jheel is a wetland of impressive potentials of harboring rich avian bio-diversity in the accompaniment of enhanced habitat reconstruction and improvement. It is located in the National Capital Region, nearby Sohana town in Gurgaon district in Haryana merely 45 Kms from Dhaula Kuan in New Delhi. At present, compared to Sultanpur National Park, it is confronting neglect. Considering its positive features of terrain, water sheet, it has the qualities of being a rich habitat for birds of all hues including the winter migratory birds. The present studies focus attention on its avian biodiversity as well as its own degraded form and structure. In all, 128 species of birds belonging to 15 orders and 41 families could be enlisted. Order Passeriformes is the predominant one having 54 species, followed by Charadriiformes (14 Species) and Ciconiiformes (12 Species). The prominent winter migratory birds observed from Damdamma Jheel include Asian Openbill Stork Anastomus oscitans, Eurasian Spoonbill Platalea leucorodia, Northern Shoveller Anas clypeata, Northern Pintail Anas acuta, Common Teal Anas crecca, Common Pochard Aythya ferina, Gadwall Anas strepera, Spot-billed Duck Anas poecilorhyncha, Spotted Redshank Tringa erythropus, Common Redshank Tringa tetanus, Common Greenshank Tringa nebularia, Kentish Plover Charadrius alexandrinus, White-tailed Lapwing Vanellus leucurus, Marsh Sandpiper Tringa stagnatilis, Wood Sandpiper Tringa glareola, Common Sandpiper Actitis hypoleucos, White Wagtail Motacilla alba and Yellow Wagtail Motacilla flava. The lake is suffering from water scarcity considering its capacity and potential to have more water. The periphery towards east is plagued by the growth of peats. The very fact that in October 2012, a large group of Openbill Stork (Nearly 70-80) has already arrived at Damdamma Lake since September-2012 indicates that it is the largest HARBOUR of Open-bill Stork in Haryana. Also, Eurasian Spoonbills were seen in a group 10-12, again the largest in Haryana. It is argued in this paper, that Damdamma is the pride lake of Haryana and prime harbor for uncommon winter migratory birds like Open-bill Stork and Eurasian Spoonbill must be the prime place for habitat reconstruction by Ministry of Environment and Forest, Govt. of India in conjunction with Govt. of Haryana with the active contributions by WWF (India) to add to the might vastness of this lake an element of grace and glory so as to conserve the winter migratory birds during their sojourn in India. In addition, it will be one nodal point to include Sultanpur National Park, Badkhal Lake, Bhindawas and Keoladeo National Park as an eco-tourism rectangle with provision for night halt.